Analysis of Income from the Transfer of Paddy Rice Fields to Chili Commodity Land in Toboino Village, East Wasile District, East Halmahera Regency - Ekaria, Ekaria; Kamisi, Haryati La; Muhammad, Munawir; Marsaoly, Hasrul A.; Masuku, Iswan (Agrikan: Jurnal Agribisnis Perikanan, 2021)
In Toboino Village, East Wasile District, East Halmahera Regency, the production of lowland rice has decreased due to land conversion from lowland rice plants to chili plants because the selling price is higher than lowland rice. This study aims to analyze the income and feasibility of changing the function of paddy fields to chili commodity land. This research was conducted in Toboino Village from March to June 2021. The analytical method used in this study is the analysis of income and farming feasibility. The results showed that the average income of lowland rice farming before land conversion was Rp. 10,077,080 per planting season/ha with an R/C ratio/feasibility of farming 2.2, and income after land conversion into chili commodity was Rp. 19,314,634 per planting season/ha with an R/C ratio/feasibility value of 2.9.